Research trends in task-based language teaching: A bibliometric analysis from 1985 to 2020 - Qin, Jie; Lei, Lei (Studies in Second Language Learning and Teaching, 2022)
This study offers a bibliometric analysis of research trends in task-based language teaching (TBLT) from 1985 to 2020. The analysis covers research questions related to the publication trends, venues for publication, productive authors, highly cited articles and references and, more importantly, the most frequently explored TBLT-related topics and their developmental patterns across the past 35 years. Results showed that TBLT was still mostly approached from the traditional cognitive-interactionist and psycholinguistic perspectives with a focus on tasks, individuals (i.e., learners and teachers), task-related variables (e.g., task complexity and task repetition), task performance, and the resultant linguistic forms. While this field of research has witnessed a growing interest in learners’ individual differences and computer-mediated, technologies-assisted learning, a decreasing trend has been observed in topics related to error and recast. Implications for task-based research, pedagogy, and research methodologies are discussed.